TikTok Integration in English Learning: Its Impact on Students’ Speaking Achievement - Nurul Syafa; Ari Wibowo (INTERACTION: Jurnal Pendidikan Bahasa, 2024)
This study aimed to investigate the impact of TikTok integration on students’ speaking achievement at SMAN 2 Sorong Regency, West Papua. Many senior high school students struggle with English speaking due to limited practice opportunities, low confidence, and lack of motivation. To address this issue, the researcher implemented TikTok as a digital learning platform to provide students with engaging opportunities to practice speaking English creatively and independently. This research employed a pre-experimental quantitative design using a one-group pre-test and post-test model. The population consisted of eleventh-grade students during the 2023/2024 academic year, with 30 students selected through purposive sampling. A speaking test was administered before and after six sessions of TikTok-based learning activities. Students’ performances were evaluated in terms of fluency, pronunciation, vocabulary, grammar, and confidence using a standardized speaking rubric. The results revealed a significant improvement in students’ speaking scores after the treatment. The mean score increased from 57.13 in the pre-test to 76.47 in the post-test, with a significance value of 0.000 (< 0.05), indicating that TikTok integration had a positive effect on students’ speaking achievement. Students became more confident, fluent, and expressive in using English as they practiced through video recording, peer feedback, and self-reflection. The study concludes that TikTok can serve as an effective and motivating tool for enhancing students’ speaking ability. It offers teachers a creative approach to integrate technology into English instruction and provides students with enjoyable, authentic opportunities to communicate in English.